Drone tracking and localization in indoor 3D environment - Khamis, Rashid Omar (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Radio Frequency Identification (RFID) is an information exchange technology based on RF communication. It is also provide solution to track and localize objects in the indoor environment. When RF transmitter is connected to the object, tracking and positioning can be performed using a wireless communication system. The technique that RF uses to locate objects is called RFID and labeled objects are called RFID tags.The technological progress has made the use of RFID tags without batteries and called passive tags, capable of recovering energy from the incoming RF signal. The reader can use the RF signal to transfer information from the reader to the tag. The tag antenna reflects a certain amount of energy that is being taken. By modulating this reflection, tags can send information. Tracking and localization of a mobile objects in an indoor environment have great significant attention due to the need of higher localization accuracy. RSS-based localization techniques are the major tools for tracking applications. This research work propose the method of localization that uses the RFID tagged drone combined with RSS value to improve the RFID based localization in indoor environment. This method provides solutions for the drone tracking problem. By measuring the RSS value between RFID tagged drone and reader, and calculate the distance between the tagged drone and atleast three readers using trilateration approach. Readers location are known and any error in measuring the distance influence drone location estimate. The localization method is implimented in MATLAB to simulate and evalute the performance of the proposed method. In this research work, localization method is implemeted to track the drone position with low localization error. The simulation environment is developed to evaluate the performance of the multiple RFID readers and the results have been compared. The localization error achieved with 4 multiple RFID readers and 8 multiple RFID readers were 0.81289 and 0.39793 meter respectively. The performance of the localization method is also compared with other RFID localization previous related works. The results have shown that the performance in localization and tracking of tagged drone in indoor environment has been improved by 42.9% when 8 multile RFID readers are applied in the localization area.